Clinical and Endoscopic Significance of Bowel-Wall Thickening Reported on Abdominal Computed Tomographies in Symptomatic Patients with No History of Gastrointestinal Disease. Issue 1 (February 2014) - Al-Khowaiter, Saad S.; Brahmania, Mayur; Kim, Edward; Madden, Mark; Harris, Alison; Yoshida, Eric M.; Gray, James R.
Background: Bowel-wall thickening (BWT) is a commonly reported finding on diagnostic abdominal pelvic computed tomographies (CT) in patients with no history of gastroenterologic disease. The significance of this nonspecific finding is not clear. Methods: Medical records from the Vancouver General Hospital were reviewed from October 27, 1999, to October 27, 2009. The initial search yielded 5696 cases, of which 76 cases met the inclusion criteria for review. Inclusion criteria were the following: age older than 18 years, symptoms without a diagnosis of gastrointestinal disease before CT, the reported finding of terminal ileal and/or colonic BWT, colonoscopy after CT, and/or microbiologic investigations. Exclusion criteria included known gastrointestinal disease before CT. The primary objective was to determine if BWT could be associated with a significant endoscopic pathology. The secondary objective was to determine whether the pattern of abnormality on the CT was associated with a specific endoscopic finding. Results: A total of 76 patients met the inclusion criteria of our study. Of those, 76% had various identifiable pathologies on colonoscopy. Only 24% had normal colonoscopic findings. Inflammatory bowel disease (IBD) and infectious colitis were the most common causes of BWT. A report of "skip lesions" on the CT (5%) was always associated with IBD. "Pancolitis" reported on the CT (11%) was associated with endoscopic findings of IBD in 25% of cases, infection in 50% of cases, and normal findings in 25% of cases. The report of "stranding" (36%) on CT in the presence of BWT was associated with many non-neoplastic endoscopic pathologic processes, including infectious colitis (22%), IBD (19%), and ischemia (15%), but also was associated with normal endoscopic findings in 26% of the cases. "Lymphadenopathy" was reported in 17% of the CTs and was associated with infectious colitis (30%), IBD (38%), or neoplastic processes (15%) but also normal endoscopic findings in 15%. Conclusion: Symptomatic patients who are found to have nonspecific BWT on CT should undergo definitive endoscopic investigation because the majority will have significant gastroenterologic disease, and only a minority will have a normal colonoscopy.